UHPLC–MS/MS analysis of sphingosine 1‐phosphate in joint cavity dialysate and hemodialysis solution of adjuvant arthritis rats: Application to geniposide pharmacodynamic study. (21st March 2019) - Xuejing, Dai; Wenyu, Wang; Hong, Wu; Zhengrong, Zhang; Li, Dai; Jun, Fu; Ran, Deng; Feng, Li; Yan, Wang; Xiang, Zhan
Abstract: Geniposide (GE) is an iridoid glycoside compound with anti‐inflammatory effect. The potential of sphingosine 1‐phosphate (S1P) as a plasma marker in human diseases was suggested recently in the literature, which demonstrated that, in patients with inflammatory diseases, plasma S1P was elevated. It follows that the obstructive coronary artery disease can be predicted with serum S1P. Therefore, S1P can also be potentially used as a pharmacodynamic marker to study adjuvant arthritis (AA) rats. In the current study, a UHPLC–MS/MS method combined with the microdialysis sampling technique (using FTY720 phosphate as an internal standard) was adopted and validated to measure S1P levels in the hemodialysis fluid and joint cavity dialysates of AA rats after oral administration of GE. A S1P concentration–time curve in the dialysate was established in this study. It was demonstrated that GE exerted an anti‐inflammatory effect by reducing AA‐induced elevated S1P levels. It is showed that changes in S1P concentrations over time can be used to monitor the pharmacodynamic effects of GE in treating AA rats in pharmacodynamic studies.